SCIENTIFIC STUDY OF RELIGIONS: SOME METHODOLOGICAL REFLECTIONS - Pathil, Kuncheria (Journal of Dharma, 1996)
The contact of the West with Islam, the revival of classical antiquity in the Renaissance with its aftermath of humanism, and the geographical discoveries of the fifteenth and sixteenth centuries with their subsequent colonial and missionary conquests, gave impetus to the study of religions of other lands and peoples. The discovery of diverse religions was experienced by western Christianity fIrst as a threat to its absolutism and only much later in recent times as an enrichment to its own growth and development. In the beginning comparative studies were always made in terms of one’s own religion, which was often taken for a norm or standard. In the second phase during the latter part of the nineteenth and the early twentieth century, there came a generation of scholars who claimed to be "neutral" or "non-committed" and who wished to make "objective" and "impartial" studies of religions. Some of them picked up isolated parallels arbitrarily from different religions all over the world. Others worked with the evolutionary principle and accordingly classified religions into higher and lower forms and. tried to reconstruct the origin and development of religion. Today these "one-track schemes of development" have been discarded by most of the scholars and emphasis has been placed on understanding the uniqueness of each religion and discovering the basic structures of the religious phenomena. This clearly manifested the necessity of a convergence of the historical and phenomenological approaches in the study of religions. In this article we do not intend to discuss these different methods or approaches in the study of religions. Our purpose here is to indicate certain guidelines to be observed in any scientific comparative study of religions. What are the rules for comparing religions?